Global analysis of proteins synthesized during phosphorus restriction in Escherichia coli. - VanBogelen, R A (1996)
The pattern of proteins synthesized in Escherichia coli during steady-state growth in media with ample inorganic phosphate (Pi), upon limitation for Pi (without an alternative phosphorous compound), and during steady-state growth in media containing phosphonate (PHN) as the sole P source was examined by two-dimensional gel electrophoresis. Of 816 proteins monitored in these experiments, all those with differential synthesis rates greater than 2.0 or less than 0.5 upon phosphate limitation (P limitation) or during growth on PHN compared with their rates in the cultures with Pi were classified as belonging to the PL or PHN stimulon, respectively. The PL stimulon included 413 proteins, 208 showing induced synthesis and 205 showing repressed synthesis. The PHN stimulon was smaller: it included 257 proteins; 227 showed induced synthesis and 30 showed repressed synthesis. The overlap of the two stimulons included 137 proteins: most (118) were ones showing induced synthesis. The promoter regions of genes for several of the proteins with induced or repressed synthesis contained sequences which resembled the consensus sequence for PhoB binding. The aggregate mass of proteins responding to P limitation or growth on PHN was 30 to 40% of the cells' total mass. By comparing the proteins responding to P limitation with those responding to growth on PHN, one can speculate which proteins are likely involved in adapting cells to new P sources or in preparing cells to survive stationary phase.